Coherence, Counterpoint, Instrumentation, Instruction in Form - Schoenberg, Arnold 1874-1951; Cross, Charlotte; Neff, Severine; Neff, Severine (Lincoln, NB University of Nebraska Press, 1994)
Only Stravinsky can claim as much credit as Schoenberg for the most dramatic innovations in twentieth-century music. Inventor of the twelve-tone row, explorer of atonality and the hexachord, composer of tone poems, songs, and chamber music, and chief spokesman for the Vienna Circle, Schoenberg has become ever more influential as his successors have come to understand him. Fuller understanding has been delayed because many of his writings have not yet been edited or published. This volume collects four short works, each concentrated on a key issue in composition. Written in 1917, but altered and augmented many times in later years, the manuscripts edited and translated in this volume have never been published before. Their importance can permit no further delay since they present Schoenberg's thinking well after the publication in 1911 of Harmonielehre, his revolutionary theoretical book. The later texts provide numerous prospects for enhancing the study and appreciation of Schoenberg's compositions and theories.
Keywords: 20th Century (1901-2000); Method; Composing; Counterpoint; Instrumentation; Twelve-tone technique